209 Survival impact of the abdominal radical trachelectomy (ART) radicality in patients with early stage cervical cancer (CC). (18th September 2019) - Soderini, A; aragona, A; Rodriguez, Y; Quintaie, A; Mendez, M; Horton, G; Moschen, H; Milone, S; Garrido, R; Martinez, D; Cuneo, N
Abstract : Objectives: To evaluate the overvall survival (OS)and disease free survival (DFS) rates related to surgical radicality in the ART sparing the uterine arteries and hypogastric plexus in patiens with early stage cervical cancer(CC). Methods: Twenty seven pts. FIGO stages Ia2 & Ib1, were included between 10/04 a 10/15. Stages Ib1 >2 cm and <4cm received neoadjuvant chemotherapy (NCH). An ART sparing the uterine arteries and hypogastric plexus was performed. Surgical radicality was compared with an historical control group of C1 radical hysterectomies. The OS& DFS rates, complications, pregnancies, recurrences, and follow-up, were analyzed. Results: The ART was performed in 25/27 patients (95, 2%). Age: 27, 5 years (25–35). Five patients received NCH. In 2 cases the procedure had to be completed with a C1RH because of positive margins in the surgical specimen. Radicality (surgical specimen): tumor size 2, 36 (1, -4, 1) cm; Vaginal length 2, 62 (0, 8–3, 1) cm; Right parametrium 3, 2 (1, 8–3, 9) cm; left parametrium 3, 04 ( 2, 3–3, 5) cm; cervix length 2, 8 (2, 3–3, 3) cm; Lymph nodes 13, 5 (2–22). No statisticaly differences were observed in surgical radicality between ART vs C1RH. Complications: 1 case of dyspareunia + cervical polyposis. 1 case of dysmenorrhea. Four pregnancies were observed. Three healthy newborns and 1 abortion were registered, all in NCH cases). Recurrences: 2/27 (8, 4%). Deaths: 2/27 (7, 3%) . DFS & OS: 92, 5%. Follow-up: 127 months (85–180). Conclusions: The ART sparing the uterine arteries and hypogastric plexus (C1 ART), showed to be feasible and oncologicaly safe. This variant of ART, could be considered as an alternative to C1RH for these initial FIGO stages.